Stage‐related implications of community‐acquired pressure injuries for the acute medical inpatients. Issue 5 (28th December 2020) - Sanson, Gianfranco; Barbin, Ilaria; De Matteis, Daniela; Marzinotto, Ilaria; Zanetti, Michela
Abstract: Aims: To analyse the prevalence of any‐stage pressure injuries at hospital admission and their impact on short‐, mid‐ and late‐term mortality. Patient characteristics associated with pressure injuries and the impact on hospital costs were also investigated. Background: In medical patients acutely admitted to hospital, no study analysed the presence of pre‐existing pressure injuries and the related short‐ and long‐term mortality according to the overall stages of severity thereof. Design: Retrospective cohort study following the STROBE guideline. Methods: In a population of 7217 acute medical inpatients, the presence and staging of pressure injuries were assessed at hospital admission. The impact of pressure injury on 30‐, 180‐ and 365‐day mortality was analysed by multivariate Cox regression models. Results: The prevalence of community‐acquired pressure injuries was 14.9% (stage‐1: 8.1%; stage‐2: 3.5%; stage‐3: 1.6%; stage‐4: 1.1%; unstageable: 0.5%). Hemiplegia/paraplegia, anaemia, poor functional status, high nutritional risk, clinical instability and systemic inflammatory response, but not hydration status, were found to be associated with the occurrence of stage‐2‐and‐above pressure injuries. An increasing difference was found in Diagnosis‐Related Groups (DRG) weight according to pressure injury stages. A distinct and progressively increasing risk‐of‐death for any‐stage pressure injury was shown after 365‐days. A significantly increased mortality risk for all considered time intervals was found for unstageable and stage‐4 pressure injuries. Conclusions: In acute medical inpatients, the presence of community‐acquired pressure injuries is part of a multidimensional clinical complexity. The presence and staging of pressure injuries have an independent dramatic impact on of early‐to‐late mortality and hospital costs. Relevance to clinical practice: This study documented as community‐acquired pressure injuries are highly prevalent and represents an independent predictor of outcomes in strict dependence of the progression of thereof stage. The presence of community‐acquired pressure injuries should be interpreted as a critical marker of frailty and increased vulnerability.